2019
DOI: 10.1017/psrm.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

Quitting globalization: trade-related job losses, nationalism, and resistance to FDI in the United States

Abstract: Existing research has found that American politicians benefit from trying to attract investment and creates jobs. In this paper, we build on this work by describing the drivers of Americans' attitudes toward inward foreign investment (FDI). We posit that foreign and Chinese investment are different than domestic investment in the public imagination and that nationalism and proximity to deindustrialization interact to shape public opinion about them. We propose and test two theories of this interaction using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
14
3
Order By: Relevance
“…Interestingly, we found no evidence that respondents were biased against China or Mexico as destinations for U.S. FDI outflows. This is in contrast to the findings of previous studies focusing on FDI inflows such as Jensen and Lindstädt (2013) and Feng, Kerner, and Sumner (2021), which found that Americans had relatively unfavorable views of Chinese investment in the United States when compared to "foreign" investment from an unspecified country. Our null findings might be attributable to the relatively small sample size, and it is possible that a statistically significant bias against China could be detected with a larger sample.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, we found no evidence that respondents were biased against China or Mexico as destinations for U.S. FDI outflows. This is in contrast to the findings of previous studies focusing on FDI inflows such as Jensen and Lindstädt (2013) and Feng, Kerner, and Sumner (2021), which found that Americans had relatively unfavorable views of Chinese investment in the United States when compared to "foreign" investment from an unspecified country. Our null findings might be attributable to the relatively small sample size, and it is possible that a statistically significant bias against China could be detected with a larger sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, several of our findings stand in contrast to the existing literature. First, unlike studies of Americans' perception of FDI inflows such as Jensen and Lindstädt (2013) and Feng, Kerner, and Sumner (2021), which showed that Americans' negative feelings toward certain countries strongly color their perception of FDI inflows from these countries, we did not find that FDI outflows to China and Mexico were more negatively perceived than FDI outflows to an unspecified "foreign" country.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Them" seeAllport (1954) andBremmer (2018), and the evidence inMutz and Kim (2017) on "in-group favoritism". The role of perceptions as to trade and income inequality also tie in with experimental studies byFeng et al (2021) according to which foreign, and especially Chinese, investment in the US is considered different than domestic investment.…”
mentioning
confidence: 95%